‘BREAKS’ Protocol for Breaking Bad News - Narayanan, Vijayakumar (Medknow Publications, 2010)
Information that drastically alters the life world of the patient is termed as bad news. Conveying bad news is a skilled communication, and not at all easy. The amount of truth to be disclosed is subjective. A properly structured and well-orchestrated communication has a positive therapeutic effect. This is a process of negotiation between patient and physician, but physicians often find it difficult due to many reasons. They feel incompetent and are afraid of unleashing a negative reaction from the patient or their relatives. The physician is reminded of his or her own vulnerability to terminal illness, and find themselves powerless over emotional distress. Lack of sufficient training in breaking bad news is a handicap to most physicians and health care workers. Adherence to the principles of client-centered counseling is helpful in attaining this skill. Fundamental insight of the patient is exploited and the bad news is delivered in a structured manner, because the patient is the one who knows what is hurting him most and he is the one who knows how to move forward. Six-step SPIKES protocol is widely used for breaking bad news. In this paper, we put forward another six-step protocol, the BREAKS protocol as a systematic and easy communication strategy for breaking bad news. Development of competence in dealing with difficult situations has positive therapeutic outcome and is a professionally satisfying one.